Feldspar/titanium dioxide/chitosan as a biophotocatalyst hybrid for the removal of organic dyes from aquatic phases. Issue 10 (13th December 2013) - Yazdani, Maryam; Bahrami, Hajir; Arami, Mokhtar
ABSTRACT Feldspar/titanium dioxide/chitosan hybrid, a photoactive biocompatible adsorbent for anionic dyes, was synthesized, characterized, and successfully tested. The adsorbent characterization, pH role, adsorbent dose effect, equilibrium data, kinetic plats, and thermodynamic parameters are reported. The point of zero charge for the hybrid was measured to be 8.3, and the most favorable pH range for the adsorption process was found to be below this pH value. The adsorption equilibrium study demonstrated that the Freundlich model was best fitted to the experimental data. Without UV light exposure, the prepared adsorbent adsorbed 72 mg of Acid Black 1 (AB1)/g of sorbent (86% removal) from a 100‐mL solution with an initial dye concentration of 50 mg/L, whereas UV irradiation resulted in an increase in the elimination of AB1 dye (97% removal). The kinetic data was depicted well by the pseudo‐second‐order model. The thermodynamic parameters indicated that the reaction between the hybrid and the dye was exothermic and also spontaneous at lower temperatures. In the batch desorption process, several aqueous solutions adjusted to different pH values were tested, and the best desorption performance (90% desorption) was achieved at pH 11. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40247.